EOSINOPHILS AND EOSINOPHIL PRODUCTS IN ASTHMA - Saeed, Waseem; Badar, Ahmed; Hussain, M Mazhar; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2002)
Eosinophils are known to be an indirect marker of airway inflammation in asthma. It is known since long that the total eosinophil count reflects asthmatic activity and is useful for regulating steroid dosage and for early detection of exacerbations. Eosinophils are currently regarded as the effector cells responsible for much of the pathology of asthma. Eosinophil-mediated damage to the respiratory epithelium is a major pathogenetic mechanism in asthma. This article is a review of the latest works about the relationship of eosinophil and eosinophil products with asthma.